SELF-EFFICACY AND QUALITY OF LIFE IN PATIENTS WITH CHRONIC KIDNEY DISEASE UNDERGOING HEMODIALYSIS - Leli Herawati; Fahrizal Alwi; Mery Silvia Harahap; Sri Wahyuni; Amel Amel (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2026)
Patients with chronic kidney disease (CKD) undergoing lifelong hemodialysis often experience declines in quality of life across physical, psychological, social, and environmental domains. The demanding treatment schedule may also lead to fatigue and reduced motivation. Self-efficacy is considered an important factor influencing patients’ ability to adapt to chronic illness. This quantitative study used a descriptive correlational design with a cross-sectional approach. The population consisted of 388 patients undergoing hemodialysis, with 80 respondents selected using purposive sampling. Data were collected using the WHOQOL-BREF and General Self-Efficacy (GSE) questionnaires. Statistical analysis was performed using the chi-square test. The findings showed a statistically significant relationship between self-efficacy and quality of life (p = 0.001; p < 0.05). Patients with higher self-efficacy tended to report better quality of life across measured domains. Self-efficacy plays a crucial role in shaping patients’ health behaviors and their ability to cope with long-term treatment demands. Strengthening self-efficacy may contribute to improved overall well-being in patients undergoing hemodialysis.